The Effect of Student Engagement to Student Academic Achievement at Faculty of Industrial Engineering Telkom University - Prihandhika Ardhian Khanifam (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2020)
To get a superior quality, human resources is certainly not in spite of the achievements, accomplishments in educational institutions can certainly be measured by the value of academic and one of the factors that may affect the achievement of learning is student engagement because when learners are able to give all his efforts to understand the material provided they are likely to have a good record. This research was conducted at the Faculty of Industrial Engineering Telkom University with student engagement as independent variables and academic achievement as the dependent variable. The purpose of this study was to determine how high student engagement, academic achievement of students as well as, to examine how high the influence of student engagement to academic achievement in students of Industrial Engineering Telkom. The respondents are 310 active students at the Faculty of Industrial Engineering Telkom University. The analysis technique used is descriptive analysis and simple linear regression. Based on the results of the study showed that student engagement at the high category and learning achievement in honors. While the statistical test results obtained that student, engagement has no effect on academic achievement in students of Industrial Engineering Telkom University.